Aislamiento social en adultos mayores: el rol de la exclusión social y la desconexión - Etchezahar, Edgardo; Gómez Yepes, Talía; Albalá Genol, Miguel Ángel; Ungaretti, Joaquín (Pontificia Universidad Católica del Perú, 2025)
Social isolation is considered a common problem in older adults and is defined as the objective lack of social contacts with others along with feelings of exclusion and isolation. 812 cases participated in this study, the average age of the participants was 67.45 years, with an age range between 60 and 80 years. Self-report measures were used through a battery of evaluation instruments composed of: Social isolation, FoMO, Feelings of social exclusion, Social disconnection and sociodemographic data. The results have shown a relationship between FoMO, social exclusion and social disconnection. The scope and limits of the findings are discussed.

El aislamiento social se considera un problema frecuente en los adultos mayores y se define como la falta objetiva de contactos sociales con los demás junto con sentimientos de exclusión y aislamiento. En este estudio participaron 812 casos, la edad promedio de los participantes fue de 67,45 años, con un rango de edad entre 60 y 80 años. Se utilizaron medidas de autoinforme a través de una batería de instrumentos de evaluación compuesta por: Aislamiento social, FoMO, Sentimientos de exclusión social, Desconexión social y datos sociodemográficos. Los resultados han mostrado una relación entre el FoMO, la exclusión social y desconexión social. Se discuten los alcances y límites de los hallazgos.

O isolamento social é considerado um problema comum em idosos e é definido como a falta objetiva de contactos sociais com outras pessoas, juntamente com sentimentos de exclusão e isolamento. Participaram deste estudo 812 casos, a idade média dos participantes foi de 67,45 anos, com faixa etária entre 60 e 80 anos. Foram utilizadas medidas de autorrelato por meio de uma bateria de instrumentos de avaliação composta por: Isolamento social, FoMO, Sentimentos de exclusão social, Desconexão social e dados sociodemográficos. Os resultados mostraram uma relação entre FoMO, exclusão social e desconexão social. O escopo e os limites das descobertas são discutidos.
Social isolation in older adults: the role of social exclusion and disconnection
Isolement social chez les personnes âgées : le rôle de l’exclusion sociale et de la déconnexion
Keywords: Elderly; Disconnection; FoMO; Social exclusion; Social isolation; Aislamiento social; Adultos mayores; Exclusión social; Desconexión; FoMO; Phubbing; Idosos; FoMO; Exclusão social; Isolamento social; https://purl.org/pe-repo/ocde/ford#5.01.00